Køn som infrastruktur - Sløk-Andersen, Beate (Kvinder, Køn & Forskning, 2011)
Gender as infrastructure. Based on the theoretical conception of ‘infrastructure' the article explores how gender can be understood in the context of the Danish information infrastructure CPR, which registers all Danish citizens. Specific to this information system is that it produces gender specific ID-numbers for citizens, which are then used to structure the Danish welfare system. Installed in this omnipotent system, the gender categories create a needed order in everyday life and, thus, become invisible. But for transgendered citizens, who live in and embody the boarderland between ‘male' and ‘female', the categories become highly visible as they become a source of suffering due to the infrastructure's requirement of clear gender categorizations, either/or. However, these categorizations can not be easily cast away as they are based on normative understandings of gender as a biological fact.